Buchanania obovata: An Australian Indigenous food for diet diversification. Issue 5 (27th May 2018) - Fyfe, Selina A.; Netzel, Michael E.; Tinggi, Ujang; Biehl, Eva M.; Sultanbawa, Yasmina
Abstract : Aim: Buchanania obovata Engl., the Green Plum, is a small green fruit eaten by Australian Indigenous peoples of the Northern Territory and Western Australia that has had limited study and has potential as a source of food for diet diversification. The flesh and seed of the fruit are eaten and the plant is used as bush medicine. Methods: Physical characteristics of the fruit were measured. The flesh and seed freeze dried powders were measured separately for proximates, mineral/trace elements and heavy metals, and folate analysis. Vitamin C was analysed in the flesh. Results: The flesh is high in protein (12.8 g/100 g dry weight (DW)) and both flesh and seed are high in dietary fibre (55.1 and 87.7 g/100 g DW, respectively). The flesh is high in potassium (2274.7 mg/100 g DW), and is a good source of magnesium (570.5 mg/100 g DW), calcium (426.0 mg/100 g DW) and phosphorous (216.8 mg/100 g DW), whereas the seed is high in iron (8.15 mg/100 g DW). The flesh contains folate at 752.4 μg/100 g DW and the seed contains 109.5 μg/100 g DW as pteroylmonoglutamic acid equivalents. Conclusions: The flesh and seed have good nutritional properties and the results support the use of the Green Plum for diet diversification and nutrition in Indigenous and non‐Indigenous populations in Australia.